PENGARUH CURRENT RATIO, DEBT TO EQUITY RATIO, RETURN ON EQUITY, DAN TOTAL ASSET TURNOVER TERHADAP DIVIDEND PAYOUT RATIO PERUSAHAAN PADA INDUSTRI MANUFAKTUR YANG TERDAFTAR DI BEI UNTUK PERIODE 2012-2013 - Martha Ayerza Esra; Reinitha Jeanne (Jurnal Ekonomi Perusahaan, 2016)
This study aims to determine the effect of the Current Ratio , Debt to Equity Ratio , Return on Equity and Total Asset Turnover on the Dividend Payout Ratio . The object of research used in this study is a company engaged in manufacturing listed in Indonesia Stock Exchange 2012-2013 period and has met the criteria established by the researchers , as many as 17 companies . The results of the analysis of this study showed that the Current Ratio and Return On Equity does not affect the Dividend Payout Ratio , while the Debt to Equity Ratio and Total Asset Turnover affect the Dividend Payout Ratio .